2022
DOI: 10.1111/1471-0528.17175
|View full text |Cite
|
Sign up to set email alerts
|

Health care in pregnancy during the COVID‐19 pandemic and pregnancy outcomes in six low‐ and‐middle‐income countries: Evidence from a prospective, observational registry of the Global Network for Women’s and Children’s Health

Abstract: Objective On a population basis, we assessed medical care for pregnant women in specific geographic regions of six countries before and during the first year of the COVID‐19 pandemic in relationship to pregnancy outcomes. Design Prospective, population‐based study. Setting Communities in Kenya, Zambia, the Democratic Republic of the Congo, Pakistan, India, and Guatemala. Population Pregnant women enrolled in the Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Significant concerns have been raised about adverse pregnancy outcomes due to COVID-19, with mixed evidence regarding stillbirths with some studies reporting an increase and some reporting no change in stillbirth rate (SBR) as a result of COVID-19 infection or lockdown 1 3–11. Much of the literature available on change in SBR is among women who had COVID-19 during pregnancy,2 3 6 8 12–15 with little evidence at the population level for births during the COVID-19 pandemic irrespective of COVID-19 during pregnancy 7 9 10 16. Large population-based estimates on pregnancy outcomes are missing from many countries with high number of cases of COVID-19, including from India 9…”
Section: Introductionmentioning
confidence: 99%
“…Significant concerns have been raised about adverse pregnancy outcomes due to COVID-19, with mixed evidence regarding stillbirths with some studies reporting an increase and some reporting no change in stillbirth rate (SBR) as a result of COVID-19 infection or lockdown 1 3–11. Much of the literature available on change in SBR is among women who had COVID-19 during pregnancy,2 3 6 8 12–15 with little evidence at the population level for births during the COVID-19 pandemic irrespective of COVID-19 during pregnancy 7 9 10 16. Large population-based estimates on pregnancy outcomes are missing from many countries with high number of cases of COVID-19, including from India 9…”
Section: Introductionmentioning
confidence: 99%
“…We divided the Global Network's COVID‐19 work into four separate studies. The first evaluated the indirect impact of the COVID‐19 pandemic on some healthcare services and the impact on several pregnancy outcomes 6 . The first observation was that although there were small reductions in physician deliveries in the first year of the pandemic, we could demonstrate no impact on any pregnancy‐related health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…These results are also similar to the previously published studies about COVID-19 pregnancies. Kumari et al reported a stillbirth rate of 2.7% (11), and another study investigating the pregnancy results of low-income countries found a 2.8% stillbirth rate during the COVID-19 pandemic (12). A prospective comparative study demonstrated the 5.1% stillbirth rate in COVID-19-infected mothers (13).…”
Section: Discussionmentioning
confidence: 98%